The role of capital and current expenditures of state and municipal governments in the Brazilian cross-state growth from 2003 to 2019 - Costa, Lorena Camilo Ximenes (2022)
We address the role played by local government spending in cross-state growth, over the widest available period from the adoption of the Fiscal Responsibility Law (FRL). We estimate an extended version of Barro-style growth panel regression in difference, controlling for exports, imports, years of schooling, enterprise and household credit. We find that the parameters associated with capital expenditures for state and municipal governments are respectively 1.23 and 5.35, while the parameters of current expenditures for state and municipal governments are -1.28 and -2.61. We do not find a significant role of municipal and state government credit.